Mapbook atlas of riparian vegetation for 2006, 2016, and the change between years - Hatcher, Emma; Young, Nicholas; Evangelista, Paul; Vorster, Tony; West, Amanda (Colorado State University. Libraries, 2017)
An ArcGIS created Mapbook atlas of the results of modeling riparian vegetation across the Colorado River Basin. The atlas includes an overview of the Colorado River Basin with these model results as well as an indexed tile-by-tile map of the results for a more detailed view. Detailed methods can be found in Woodward et al. (In prep).
Models of riparian vegetation were created by digital image sampling to collect environmental response data. National Agriculture Imagery Program (NAIP) imagery at the time step and a scripted Google Earth Engine image visualization and data collection interface was used to ocularly interpret the presence and absence of riparian vegetation. Final models were applied using Landsat composite imagery and associated vegetation indices with the digitally collected occurrence locations. The random forest algorithm was used within Google Earth Engine to develop models for 2006 and 2016 by Environmental Protection Agency (EPA) ecoregion III. Models were constrained to valley bottoms across the Colorado River Basin. A change map was created by differencing 2006 and 2016 results for a gain, loss and persistence map. Detailed methods can be found in Woodward et al. (In prep).
Users of these maps and other analysis products are solely responsible for interpretations made from these products. The Natural Resource Ecology Laboratory makes every effort to ensure this map is free of errors but does not warrant the map or its features are either spatially or temporally accurate or fit for a particular use. The Natural Resource Ecology Laboratory provides this map without any warranty, either express or implied.
Natural Resource Ecology Laboratory (NREL)
Keywords: riparian vegetation; change map; atlas; Google Earth Engine